Cross-sectional study on visual inspection with acetic acid and pap smear positivity rates according to sociodemographic factors among rural married women of bareilly (Uttar Pradesh) - Ruchi Arun; Jai Prakash Singh; Shyam Bihari Gupta (Wolters Kluwer Medknow Publications, 2018)
Background: It is possible to prevent deaths due to cervical cancer through screening and treatment. Cervical cytology which is a standard screening tool in developed countries fails as a screening method in low-resource countries due to financial and technical constraints. Objective: To determine the prevalence of pre-malignant lesions of the cervix by VIA and Pap smear test among rural married women and to find out association of socio demographic factors with positive screening test results. Method: A community based cross-sectional study was carried out among rural married women in the field practice area of a tertiary health care center. A pre-designed questionnaire was administered to collect information on socio-demographic characteristics from 550 women. They were tested for the presence of pre-malignant lesions of the cervix using VIA and Pap smear as screening tools. Results: Out of 550 study participants, total 37 patients were found positive, out of which 7, 17 & 13 patients were found positive by Pap smear alone, VIA test alone, and by both these tests respectively. Moderate agreement (k=0.498) was found between these two tests by applying Kappa statistics at 95% confidence interval. The VIA and Pap smear tests were positive among 5.5% and 3.6% study subjects respectively. The positivity rate was found to be more in the age group of >50 years, Hindu, SC/ST caste, joint family, professional and, upper class. Conclusion: The prevalence of pre-malignant lesions of the cervix by VIA test was 5.5% while 3.6% pre-malignant lesion was detected by Pap smear method. VIA and Pap smear positivity rates among rural married women.